Double Immunohistochemical Labelling of PRAME and Melan A in Slow Mohs Biopsy Margin Assessment of Lentigo Maligna and Lentigo Maligna Melanoma - R. Salih; F. Ismail; G. E. Orchard (Frontiers Media S.A., 2024)
Introduction: Lentigo maligna (LM) and lentigo maligna melanoma (LMM) predominantly affect the head and neck areas in elderly patients, presenting as challenging ill-defined pigmented lesions with indistinct borders. Surgical margin determination for complete removal remains intricate due to these characteristics. Morphological examination of surgical margins is the key form of determining successful treatment in LM/LMM and underpin the greater margin control provided through the Slow Mohs micrographic surgery (SMMS) approach. Recent assessments have explored the use of immunohistochemistry (IHC) markers, such as Preferentially Expressed Antigen in Melanoma (PRAME), to aid in LM/LMM and margin evaluation, leveraging the selectivity of PRAME labelling in malignant melanocytic neoplasms.Methods: A Novel double-labelling (DL) method incorporating both PRAME and MelanA IHC was employed to further maximise the clinical applicability of PRAME in the assessment of LM/LMM in SMMS biopsies. The evaluation involved 51 samples, comparing the results of the novel DL with respective single-labelling (SL) IHC slides.Results: The findings demonstrated a significant agreement of 96.1% between the DL method and SL slides across the tested samples. The benchmark PRAME SL exhibited a sensitivity of 91.3% in the SMMS specimens and 67.9% in histologically confirmed positive margins.Discussion: This study highlights the utility of PRAME IHC and by extension PRAME DL as an adjunctive tool in the assessment of melanocytic tumours within staged excision margins in SMMS samples.